HUMAN CAPITAL SEBAGAI STRATEGI PENINGKATAN MUTU LEMBAGA PENDIDIKAN - Jajat Darojat (Lembaga Publikasi Ilmiah, 2022)
To create a quality output, of course, a quality institution is needed. Likewise, in order to create a quality and qualified institution, it is necessary to have a managerial built based on existing quality standards. Quality problems so far, there are still many obstacles, there are no educational meetings. To this day, the problem of educational institutions is still considered problematic. It can be concluded that the national education goals have not been achieved. The problem of the quality of educational institutions is indeed varied, ranging from sources of funding, facilities or facilities, leadership, and even not a few problems that consider resources to be a burden as an institution, which does not contribute to improving the quality of the institution. Even so, it cannot be considered simple, but it takes a proof to study how strategic institutions improve their quality. In the development of management science, there are various approaches that can be used as study material, as an effort to improve quality or educational institutions. In the study of Human Resource Management, an approach has been identified that considers Human Resources as the main capital (asset) that cannot improve in improving the quality of the institution. the approach is the Human Capital approach. A Human Resource management approach that can be used as a strategy for improving the quality of educational institutions. ABSTRAK Untuk menciptakan output yang berkualitas, tentu dibutuhkan lembaga yang berkualitas pula. Begitupun seterusnya, agar terciptanya lembaga yang berkualitas dan bermutu dibutuhkan managerial yang terukur dan dibangun berdasarkan standar mutu yang ada. Persoalan mutu lembaga selama ini, masih banyak kendala yang ditemui, tidak terkecuali lembaga pendidikan. Sampai hari ini, persoalan mutu lembaga pendidikan masih dianggap bermasalah. Hal ini dapat diambil kesimpulan dari belum tercapainya tujuan pendidikan nasional. Persoalan mutu lembaga pendidikan memang bersifat variatif, mulai dari persoalan pendanaan, sarana ataupun fasilitas, kepemimpinan, bahkan tidak sedikit persoalan yang menganggap sumber daya manusia sebagai beban lembaga, yang tidak memberikan kontribusi bagi peningkatan kualitas lembaga. Anggapan demikian memang tidak bisa dianggap sederhana, namun dibutuhkan suatu pembuktian hingga kajian tentang bagaimana strategi lembaga dalam meningkatkan mutunya. Dalam perkembangan ilmu manajemen, ada berbagai pendekatan yang dapat dijadikan bahan kajian, sebagai upaya peningkatan kualitas atau mutu lembaga pendidikan. Dalam kajian Human Resource Management telah dikenalkan sebuah pendekatan yang menganggap Sumber Daya Manusia itu adalah sebagai modal utama (asset) yang tidak bisa digantikan dalam meningkatkan mutu lembaga. pendekatan tersebut adalah pendekatan Human Capital. Suatu pendekatan manajemen Sumber Daya Manusia yang dapat digunakan sebagai strategi peningkatan mutu lembaga pendidikan.